Tetraarylpyrrolo[3,2-b]pyrrole-BODIPY dyad: a molecular rotor for FRET-based viscosity sensing - Agrawal, Richa; Gorai, Sudip; Yadav, Sunil Suresh; Wadawale, Amey P.; Mula, Soumyaditya (Frontiers in Chemistry, 2024)
With the aim to develop a FRET based viscosity sensor, two dyad molecules, 4 and 5, comprising of tetraarylpyrrolo[3,2-b]pyrrole (TAPP) (donor) and naked boron-dipyrromethene (BODIPY) dyes (acceptor) were designed. Dyads were synthesized via acid catalysed multicomponent reactions followed by Sonogashira coupling. In both the dyads, BODIPY and TAPP moieties are linked through phenylethynyl groups which allow free rotation of the BODIPY dyes i.e. they can act as molecular rotors. This was supported by X-ray crystallographic and DFT optimized structures. Spectroscopic studies also confirmed the presence of both TAPP and BODIPY dyes in dyads with no electronic interactions which is suitable for fluorescence resonance energy transfer (FRET). Very high energy transfer efficiency (ETE >99%) from donor TAPP moiety to acceptor BODIPY moiety on excitation at the TAPP part was observed. But due to the non-fluorescent nature of naked BODIPY dyes, no fluorescence emission was observed from BODIPY moiety in both the dyads. But, with increasing solvent viscosities, emission from the BODIPY moieties increases due to restricted rotation of the BODIPY moieties. Plot of logarithms of fluorescent intensity of dyad 5 and viscosity of the solution showed a good linear correlation obeying Förster-Hoffmann equation. Non-fluorescent dyad 5 in methanol became greenish yellow fluorescent in methanol/glycerol (1:1) solvent. Further, with increase in temperature of methanol/glycerol (1:1) system, as the viscosity decreases, the fluorescence also starts decreasing. Thus, the dyad 5 is capable of sensing the viscosity of the medium via FRET based “Off-On” mechanism. This type of viscosity sensor with very large pseudo-Stokes shift and increased sensitivity will be useful for future advancement of chemo-bio sensing and imaging applications.